Sequência rápida de intubação em pediatria: Atualização e proposta de protocolo - Ana Paula Cauduro Couto; Adriana Koliski; Wendell Paiva Vita; Marcelo Rodrigues (Sociedade Brasileira de Pediatria, 2023)
Endotracheal intubation is a frequent procedure in intensive care units and emergency care. The rapid intubation sequence (SRI) consists of a series of steps for sequential administration of sedative drugs and neuromuscular blockers, providing the ideal conditions for endotracheal intubation. The objective of this study is to carry out a bibliographic review of the medications used in pediatric SRI, and to propose the institution of an updated protocol that includes a safe analgesic medication. It is suggested to include dextrocetamine or fentanyl, depending on the clinical condition, for SRI.